“Nothing Is Gonna Change If We Don't Care for Everyone”: A Narrative Inquiry Alongside Urban Indigenous Youth in an Afterschool Physical Activity Wellness Program - Lewis, Brian; Schaefer, Lee; Lessard, Sean; Koch, Jordan (Frontiers in Sports and Active Living, 2022)
In the fall of 2013, the authors received funding to help develop and implement an after-school wellness program alongside Indigenous youth aged 6-10 years old in the North Central neighbourhood of Regina, Saskatchewan, Canada. The after-school program was funded, in part, as a corrective response to a broader social trend in which Indigenous youth in this neighbourhood reported declining health and wellness outcomes, as well as multiple other barriers to social inclusion. This article discusses the reflections of three senior high Indigenous youth (16-18 years old) who participated in the after-school program as peer-mentors over a two-year period from 2015-2017. Adopting narrative inquiry as our primary methodology, our analysis reveals how these youth viewed the program—and their role(s) within it—in far more complex, active, and even political terms, than the program’s initial framing as a physical activity-based ‘intervention’ had anticipated. Our analysis (re)positions youth according to their own personalized voice and narratives as: cultural leaders, knowledge holders, and as agents of change in their community.